Uneven-aged and even-aged forest management shape the soil fungal community composition in a boreal Norway spruce (Picea abies Karst) forest - Roth, Eva-Maria; Sietiö, Outi-Maaria; Valkonen, Sauli; Tuittila, Eeva-Stiina; Helmisaari, Heljä-Sisko; Karhu, Kristiina (Elsevier, 2025)
Forest management alters stand density, microclimate, and litter accrual, which all affect soil fungi. Mycorrhizal fungi play a key role in soil organic carbon (C) accumulation in boreal forests. We aimed to compare how uneven-aged continuous cover forestry (CCF) and even-aged rotation forest management (RFM) affect the soil fungal community, to draw conclusions on possible effects for long-term soil C storage. We compared uncut boreal Norway spruce forests to mature uneven-aged (CCF), even-aged and clear-cut forests (the latter two representing late and early stage in RFM). We compared their fungal community composition, species richness and diversity based on metabarcoding of bulk soil samples using sequences of the fungal ITS2 regions, and analysed the response of saprotrophic, ecto- and ericoid mycorrhizal fungal guilds to management practice. We found that fungal communities differed between all treatments, but species richness and diversity were not impacted. Clear-cuts were most dissimilar to the other treatments and the organic layer was more affected than the mineral soil. Abundance, diversity and richness of ectomycorrhizal fungi was declined in clear-cuts, leading to dominance of saprotrophic fungi. The abundance of functional guilds in even-aged and uneven-aged stands were similar to those in uncut stands. Ericoid mycorrhizae were more abundant in both stages of RFM, but their community composition was not affected by the forest management type. Despite the altered potential functionality, we found similar C stocks and cellulose decomposition rates in all treatments. This highlights the functional redundancy in the fungal community. Therefore, we conclude that CCF is unlikely to change the long-term soil C storage compared to unmanaged forests. The long-term effects of multiple clear-cutting cycles in RFM on the ecological functionality and possible effects on soil C storage should be further studied for example with sites that have been clear-cut more than once.
Keywords: metsämaa; maaperän hiili; mykorritsasienet; jatkuva kasvatus